Binge eating in obese children and adolescents. - Decaluwé, V; Braet, C; Fairburn, C (2003)
OBJECTIVE: The first goal of the current study was to examine the extent to which a population of obese children and adolescents have developed binge eating problems. The second goal was to generate variables that would distinguish obese binge eaters from obese non-binge eaters. METHOD: A group of 126 children and adolescents seeking residential care because of their obesity was selected. A self-report version of the Eating Disorder Examination was administered. RESULTS: Binge eating episodes were reported by 36.5% of the obese youngsters. Six percent reported two or more episodes of binge eating a week. Obese binge eaters differed significantly from obese non-binge eaters in self-esteem and in a broad range of eating-related characteristics. Compared with obese non-binge eaters, the obese binge eaters were slightly younger. Obese binge eaters did not differ from obese non-binge eaters in degree of overweight or depression. DISCUSSION: Results suggest that binge eating is a prevalent problem among obese children and adolescents seeking help for their obesity. The marked difference between obese children with and without binge eating suggests the need for special treatment to focus on the problems of obese binge eaters.